2013
DOI: 10.1039/c3ay40083b
|View full text |Cite
|
Sign up to set email alerts
|

Real-time diesel particulate monitor for underground mines

Abstract: The standard method for determining diesel particulate matter (DPM) exposures in underground metal/ nonmetal mines provides the average exposure concentration for an entire working shift, and several weeks might pass before results are obtained. The main problem with this approach is that it only indicates that an overexposure has occurred rather than providing the ability to prevent an overexposure or detect its cause. Conversely, real-time measurement would provide miners with timely information to allow eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The monitoring solutions developed for respirable coal dust [1, 2] diesel particulate matter, [3] and respirable dust enhanced by video features [4] are aimed at gathering near real-time information of the aerosol concentration levels during the shift. Unfortunately, these solutions do not address the monitoring of respirable crystalline silica (RCS) in the mining environment.…”
Section: The Occupational Monitoring Needmentioning
confidence: 99%
“…The monitoring solutions developed for respirable coal dust [1, 2] diesel particulate matter, [3] and respirable dust enhanced by video features [4] are aimed at gathering near real-time information of the aerosol concentration levels during the shift. Unfortunately, these solutions do not address the monitoring of respirable crystalline silica (RCS) in the mining environment.…”
Section: The Occupational Monitoring Needmentioning
confidence: 99%
“…Nowadays, PM and elemental carbon (EC) concentrations in mines can be determined by real-time measurement techniques (Kimbal et al 2012;Noll et al 2013), but traditionally, the mass and composition of particles have been investigated by collecting particles on filters or impactor substrates, and the mass and chemical species have been determined in the laboratory (Verma et al 1994;McDonald et al 2002). Advanced online methods, such as aerosol mass spectrometers (AMS; Jayne et al 2000), have originally been developed for investigation of the chemical composition of atmospheric submicrometer particles.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding BC, 4-12% of measured BC was attributed to blasting at the sites excluding the blasting area where 45% of BC was associated with blasting. Traditionally, BC has been used as a tracer for diesel emissions in the mines (Noll et al, 2007(Noll et al, , 2013, but as shown in the present study, also blastings can produce BC in the mines. However, the contribution of blasting to the BC concentrations was significant only at the blasting site.…”
Section: Sources Of Pm1 In the Minementioning
confidence: 72%